Hyperoxia Improves Hemodynamic Status During Head-up Tilt Testing in Healthy Volunteers: A Randomized Study. Issue 8 (February 2016) - Fromonot, Julien; Chaumet, Guillaume; Gavarry, Olivier; Rostain, Jean-Claude; Lucciano, Michel; Joulia, Fabrice; Brignole, Michele; Deharo, Jean-Claude; Guieu, Regis; Boussuges, Alain
Abstract : Abstract: Head-up tilt test is useful for exploring neurally mediated syncope. Adenosine is an ATP derivative implicated in cardiovascular disturbances that occur during head-up tilt test. The aim of the present study was to investigate the impact of hyperoxia on adenosine plasma level and on hemodynamic changes induced by head-up tilt testing. Seventeen healthy male volunteers (mean age 35 ± 11 years) were included in the study. The experiment consisted of 2 head-up tilt tests, 1 session with subjects breathing, through a mask, medical air (FiO2 = 21%) and 1 session with administration of pure oxygen (FiO2 = 100%) in double-blind manner. Investigations included continuous monitoring of hemodynamic data and measurement of plasma adenosine levels. No presyncope or syncope was found in 15 of the 17 volunteers. In these subjects, a slight decrease in systolic blood pressure was recorded during orthostatic stress performed under medical air exposure. In contrast, hyperoxia led to increased systolic blood pressure during orthostatic stress when compared with medical air. Furthermore, mean adenosine plasma levels decreased during hyperoxic exposure before (0.31 ± 0.08 μM) and during head-up tilt test (0.33 ± 0.09 μM) when compared with baseline (0.6 ± 0.1 μM). Adenosine plasma level was unchanged during medical air exposure at rest (0.6 ± 0.1 μM), and slightly decreased during orthostatic stress. In 2 volunteers, the head-up tilt test induced a loss of consciousness when breathing air. In these subjects, adenosine plasma level increased during orthostatic stress. In contrast, during hyperoxic exposure, the head-up tilt test did not induce presyncope or syncope. In these 2 volunteers, biological study demonstrated a decrease in adenosine plasma level at both baseline and during orthostatic stress for hyperoxic exposure compared with medical air. These results suggest that hyperoxia was able to increase blood pressure during head-up tilt test via a decrease in plasma adenosine concentration. Our results also suggest that adenosine receptor antagonists are worth trying in neurocardiogenic syncope.